Can Market Failure Cause Political Failure - ANEY, Madhav S. (Institutional Knowledge at Singapore Management University, 2010)
How can market failure interact with choice of institutional reform made by an electorate? We study this question in the framework of occupational choice where agents are endowed heterogeneously with wealth and talent. In our model, market failure due to unobservability of talent endogenously creates a class structure that affects vote on institutional reform. We find that the preferences of these classes may be highly nonmonotonic in wealth and are often aligned in ways that creates a tension between institutional reforms that are growth maximising and those that are politically feasible. This is in contrast to the world without market failure where the electorate unanimously vote in favour of surplus maximising institutional reform. We find that inefficiencies of market failure may be further amplifed by political choices made by interest groups created in the inefficient market.